Differential proteomic expression in indolent vulvar lichen sclerosus, transforming vulvar lichen sclerosus and normal vulvar tissue. Issue 12 (26th August 2022) - Gleue, Casey A.; Xie, Fangyi; Deschaine, Maria; Dasari, Surendra; Sartori‐Valinotti, Julio C.; Torgerson, Rochelle R.; Davis, Mark D. P.; Charlesworth, M. Cristine; Meves, Alexander; Lehman, Julia S.
Abstract: Vulvar lichen sclerosus (VLS) confers approximately 3% risk of malignant transformation to vulvar squamous cell carcinoma (VSCC). We used unbiased proteomic methods to identify differentially expressed proteins in tissue of patients with VLS who developed VSCC compared to those who did not. We used laser capture microdissection‐ and nanoLC‐tandem mass spectrometry to assess protein expression in individuals in normal vulvar tissue (NVT, n = 4), indolent VLS (no VSCC after at least 5 years follow‐up, n = 5) or transforming VSCC (preceding VSCC, n = 5). Interferon‐γ and antigen‐presenting pathways are overexpressed in indolent and transforming VLS compared to NVT. There was differential expression of malignancy‐related proteins in transforming VLS compared to indolent VLS (CAV1 overexpression, AKAP12 underexpression), particularly in the EIF2 translation pathway, which has been previously implicated in carcinogenesis. Results of this study provide additional molecular evidence supporting the concept that VLS is a risk factor for VSCC and highlights possible future biomarkers and/or therapeutic targets.